The CREB-binding protein (CBP) cooperates with the serum response factor for transactivation of the c-fos serum response element (1997)
The serum response element is one of the major promoter elements of the immediate early response to extracellular signals. The serum response element includes two main binding sites for proteins: the Ets box, which binds p62TCF, and the CArG box, which binds p67SRF. These two proteins are direct targets for signal transduction pathways; p62TCF is a nuclear end point of the Ras/mitogen-activated protein kinase pathway, and p67SRF is targeted by the Rho/Rac small G-proteins. The mechanism by which the signal is further transduced from the transcription factors to the basal transcriptional machinery is poorly understood. Recent data have suggested that the cAMP-responsive element-binding protein (CREB)-binding protein, a transcriptional adaptor involved in the transactivation through a wide variety of enhancer elements, participates in p62TCF activity. We here show that the CREB-binding protein also cooperates in the process of transactivation by p67SRF. Cotransfections of expression vectors for the CREB-binding protein increased the expression, in response to serum, of reporters under the control of the c-fos serum response element. Interestingly, the C-terminal moiety of the CREB-binding protein was not necessary to observe this effect. The cooperation did not require the Ets box in the serum response element, and the CArG box was sufficient, indicating that the CREB-binding protein is able to cooperate with p67SRF in the absence of an Ets protein. Co-immunoprecipitation experiments using cell extracts showed that p67SRF could be retained with antibodies directed against the CREB-binding protein, suggesting that the two proteins form a multimolecular complex in live cells. The physical interaction between p67SRF and the CREB-binding protein was further confirmed by two-hybrid assays in mammalian cells. Our results indicate that the CREB-binding protein cooperates with p67SRF and, thus, suggest that the serum response element is regulated by a multimolecular complex, which includes the CREB-binding protein, p67SRF, and p62TCF, with multiple interactions between the components of the complex.